Miejsce małego ośrodka osadniczego w układzie aglomeracji - ujęcie ogólne - Łuczyszyn, Andrzej (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The development of small towns in Poland in relations to metropolitan areas has been less dynamic recently. This proces deepens as a result of the impact of external factors such as marketing of European economy or metropolisation of space. Further restrictions of functions of the state can bring pathological differentiations in peripheral areas mainly. Nowadays we can point out such areas where classic field of economy have disappeared. Contemporary policy of regional development should take into consideration problem of small peripheral areas in the first place. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1087, s. 93-99